P133 UTILITÀ DEL MYOCARDIAL WORK NELLA VALUTAZIONE ECOCARDIOGRAFICA MULTIPARAMETRICA DI PAZIENTI CON CARCINOMA MAMMARIO. (18th May 2022) - Di Lisi, D; Madaudo, C; Rossetto, L; Di Palermo, A; Gambino, G; Buccheri, G; Damerino, G; Di Leo, G; Galassi, A; Novo, G
Abstract: Background: The aim of our study was to assess subclinical cardiac effects of anthracyclines (ANTs) in women treated for breast cancer (BC). Methods: We enrolled 46 female patients with BC undergoing adjuvant treatment with anthracycline–containing chemotherapy (CT) followed by taxane (paclitaxel/docetaxel). Patients underwent physical examination, electrocardiogram (ECG) and standard transthoracic echocardiography (TTE) including evaluation of diastolic and systolic function, measured as left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (GLS) and myocardial work (MW) expressed as global work index (GWI), global constructive work (GCW), global work waste (GWW), and global work efficiency (GWE). The parameters were measured at baseline (T0) and at 3 months (T1) and 6 months (T2) follow up. Results: All patients completed the chemotherapy cycles. No significant cardiovascular adverse events were observed during treatment. Neither 2D left ventricular ejection fraction (LVEF) nor E/e' ratio evaluation at TDI were significantly changed after treatment. Conversely, GLS was significantly reduced at T1 and T2 since baseline (GLS – 19, 99 % IQR –20, 6 –19, 3 % at T0 vs –17, 88 % IQR –18, 8 –16, 9 % at T1, p < 0, 00 1 and –16, 71 % IQR 17, 6 –15, 7 % at T2, p < 0, 001). Consensually, a significant reduction in myocardial work was also measured (GWI 2115 mmHg% IQR 1888 – 2342 mmHg% at T0 vs 1714 mmHg% IQR 1557 – 1870 mmHg% at T1, p < 0, 0001 and 1694 mmHg% IQR 1482 – 1907 mmHg% at T2, p < 0, 0001). Conclusion: Our study demonstrates that evaluation of myocardial work allows very early detection of subclinical cardiac damage induced by chemotherapy, consensually to the reduction of the GLS. A multiparametric assessment of the myocardial function, including myocardial work and GLS, could improve the accuracy of risk stratification of cardiotoxicity in patients undergoing ANTs treatment.